Data and code for the paper SCAR and the Antarctic Treaty System – an evidence-based perspective - Steven Chown; Kees Bastmeijer; Cassandra M Brooks; Neil Gilbert; Laura Phillips; Akiho Shibata (2023)
Details of and counts of Working Papers and Information Papers submitted to the Antarctic Treaty Consultative Papers from 1961 to 2023, including the names of the authors (country Parties, Observers, Experts) along with metadata describing the contents of the files and R code used for the analyses of these data. All data were collected and analysed as described in the associated text file over the period August to September 2023.